Human Rights Protection in the Digital Sphere: The Problematics of Legal Certainty and Its Relevance to the SDGs - Yosua Nicholas Tan; Abdurrakhman Alhakim; Nurlaily Nurlaily (CV. Social Politic Genius (SIGn), 2026)
The transformation of digital technology creates a conflict between the guarantee of freedom of expression and the protection of the right to privacy within the national legal system. The reform of electronic regulations has been shown to leave grammatical weaknesses, such as multi-interpretable provisions, ambiguity in protection instruments for human rights defenders, and a vacuum of norms for responding to artificial intelligence innovations. This research aims to evaluate the challenges of legal certainty in the governance of the digital sphere in Indonesia and to develop a harmonization framework for national legal instruments to align with the SDG targets. This research is a normative legal study applying the statute and conceptual approaches to qualitatively analyze legal materials through grammatical and systematic interpretation. The research results show that existing regulations fail to provide legal certainty because there is no absolutely independent supervisory authority. The subordination of the data protection supervisory institution to executive power undermines the objectivity of sanction enforcement and reveals structural flaws that contradict the principle of global institutional justice. Therefore, lawmakers are recommended to immediately overhaul the supervisory authority’s design to make it independent and mandate the implementation of human rights impact assessments for all electronic system operators to realize an equitable digital ecosystem.